Effect of a weight loss program on serum adiponectin and insulin resistance among overweight and obese premenopausal females - Walaa H. Foula; Rana H. Emara; Mona K. Eldeeb; Samiha A. Mokhtar; Fikrat A. El-Sahn (SpringerOpen, 2020)
Abstract Background Obesity has emerged as a public health crisis in many populations including Egypt. Adipose tissue produces a number of adipokines, one of them is adiponectin which has attracted much attention because of its antidiabetic and antiatherogenic effects. Objective To determine the effect of a weight loss program on serum adiponectin level and insulin resistance among overweight and obese adult premenopausal females. Study design A pre-postintervention study was carried out among 95 premenopausal overweight and obese females (body mass index ≥ 25 kg/m2) aged 20 to 40 years at the integrated health clinic affiliated to the High Institute of Public Health, Alexandria, Egypt, from February 2016 to February 2017. All participants underwent a weight loss program based on a reduced calorie balanced diet and advised to increase their physical activity. Dietary instructions and follow-up were done weekly throughout 16 weeks. Blood samples were collected to investigate serum adiponectin level and insulin resistance at the beginning and the end of the intervention. Results After 16 weeks, a significant decrease in body weight by 9.7% was associated with a significant increase in serum adiponectin from 13.3 ± 4.9 μg/ml to 18.5 ± 5.6 μg/ml. Both fasting insulin and insulin resistance had decreased significantly by 13.6% and 13.7%, respectively. Conclusion A weight reduction program depending on a reduced calorie diet for 16 weeks was associated with a significant increase in total adiponectin level and reduction in insulin resistance. An emphasis on the importance of keeping normal weight through nutritional education and the promotion of healthy diets is recommended to reduce the risk of occurrence of insulin resistance, type 2 diabetes, and cardiovascular diseases.